Characterization and transformation of the CabHLH18 gene from hot pepper to enhance waterlogging tolerance - Tian, Huaizhi; Fan, Gaoling; Xiong, Xingwei; Wang, Hui; Zhang, Suqin; Geng, Guangdong (Frontiers in Plant Science, 2024)
Basic helix-loop-helix (bHLH) proteins are important in abiotic stress control. Here, a specific bHLH transcription factor gene, CabHLH18, from a strong waterlogging-tolerant pepper cultivar, “ZHC2” was successfully cloned. The CabHLH18 gene presented a coding sequence length of 1,056 bp, encoding 352 amino acids, and the protein was the closest to Capsicum annuum XM016694561.2 protein. The CabHLH18 protein was located in the nucleus. Transformation of the CabHLH18 overexpression vector into the plumules of hot peppers, “DFZJ” and “ZHC1,” exhibited 21.37% and 22.20% efficiency, respectively. The root length, plant height, and fresh weight of the “DFZJ” overexpression lines were greater than those of wild-type (WT) plants under waterlogging conditions. Compared with the WT plants, the overexpression lines generally showed greater contents of water, the amino acid, proline, soluble sugar, root viability, and superoxide dismutase activity, but lower malondialdehyde content under waterlogging conditions. Plant fresh weight, amino acids, proline, and soluble sugar levels of the overexpression lines were 39.17%, 45.03%, 60.67%, and 120.18% greater, respectively, compared with the WT plants at 24 h after waterlogging stress. Therefore, the CabHLH18 gene could be implicated in conferring waterlogging tolerance in hot peppers, and holds promise for enhancing their overall waterlogging tolerance.